From high hopes to shattered dreams? the second Mahathirist revolution - Azly Rahman (Strategic Information and Research Development Centre Azly Reka, LLC, 2020)
What is the meaning of Mahathir Mohamad's return as Prime Minister of Malaysia? And what does it mean for the future of the country? In From High Hopes to Shattered Dreams? Azly Rahman argues that, as against a more fundamental transformation of Malaysian society, the change of government which took place post-GE14 has continued to reproduce old trends which have long kept Malaysia from the promise of an equal and forward looking nation, from a feudal mentality, to religious exclusivism, racial divisiveness and the continuing 'bumi agenda'. Diagnosing these issues through the lens of cultural theory, Azly advocates for a more fundamental change which transcends politics and which allows for the development of a truly critical consciousness in the country, one capable of producing future-oriented citizens who understand the true meaning of freedom. In a final section, containing three original essays, he then calls for a Third Force to develop beyond BN and Mahathirism, to help produce a country that is sustainable, politically, socially, economically and environmentally.